Implant Failure: Know and Prevent - Shah, Rohit; Yadav, Amitabh; Mitra, Dipika; Rodrigues, Silvia; Shetty, Gaurav; Prithyani, Saurabh; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
Failures are stepping stones to success. Implant failures are now increasingly becoming common, hence a better understanding of the factors associated with implant failures will help prevent and facilitate clinical decision making and may enhance implant success. This review article summarizes and classifies implant failures into early and late failures, surgical and prosthetic failures, hence simplifying the protocol to help prevent and manage the same.